Assistance in Child Feeding Influences the Nutritional Intake of Stunting Children: Randomized Control Trial - Hj. Sukmawati, 1,2 Sirajuddin2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background. Basic Health Research (BHR) in 2018 noted the prevalence of stunting in Indonesia was still high 30.8%, and around 8.9 million Indonesian children stunted. The Province of South Sulawesi ranks the fourth highest stunting prevalence of all provinces in Indonesia. Nutrition Status Monitoring (NSM) results in the last three years show the percentage of stunting children in South Sulawesi in 2015, 2016 and 2017 was 34.1%, 35.6%, and 34.8%. Objective: This study wants to investigate effect of assistance in child feeding for stunting children to nutrient intake and weight gain. Method: The Randomized Control Trial (RCT). The sample is stunting children aged 2-3 years. There were 30 children (15 as the intervention and 15 as the control group). Study location in the Paccerakang Community Health Center in Makassar City. Statistical analysis used to test hypotheses using Mann-Whitney. Results: an increase in the intake of carbohydrates, protein, vitamin A, z ink higher in the treatment group than the control group (p<0,05). Conclusion: Child feeding assistance significantly influence the nutrition intake of stunting children and also have an effect but not significantly on weight gain of stunting.